Targeting the Water Network in Cyclin G‐Associated Kinase (GAK) with 4‐Anilino‐quin(az)oline Inhibitors. (26th May 2020) - Asquith, Christopher R. M.; Tizzard, Graham J.; Bennett, James M.; Wells, Carrow I.; Elkins, Jonathan M.; Willson, Timothy M.; Poso, Antti; Laitinen, Tuomo
Abstract: Water networks within kinase inhibitor design and more widely within drug discovery are generally poorly understood. The successful targeting of these networks prospectively has great promise for all facets of inhibitor design, including potency and selectivity for the target. Herein, we describe the design and testing of a targeted library of 4‐anilinoquin(az)olines for use as inhibitors of cyclin G‐associated kinase (GAK). GAK cellular target engagement assays, ATP binding‐site modelling and extensive water mapping provide a clear route to access potent inhibitors for GAK and beyond. Abstract : Navigating water ways : To understand better how water networks influence drugs in general and kinase inhibitors in particular, we have elucidated the properties of a proposed water network with cyclin G‐associated kinase (GAK) by using a targeted point mutation 4‐anilinoquin(az)oline library. This can be used as a tool towards more potent GAK inhibitors and to enhance wider inhibitor design.